Overexpression of the WRKY transcription factor gene NtWRKY65 enhances salt tolerance in tobacco (Nicotiana tabacum) - Zhang, Xiaoquan; Zhang, Yaxuan; Li, Man; Jia, Hongfang; Wei, Fengjie; Xia, Zongliang; Zhang, Xuelin; Chang, Jianbo; Wang, Zhaojun (BMC plant biology, 2024)
Salt stress severely inhibits plant growth, and the WRKY family transcription factors play important roles in salt stress resistance. In this study, we aimed to characterize the role of tobacco (Nicotiana tabacum) NtWRKY65 transcription factor gene in salinity tolerance. This study characterized the role of tobacco (Nicotiana tabacum) NtWRKY65 transcription factor gene in salinity tolerance using four NtWRKY65 overexpression lines. NtWRKY65 is localized to the nucleus, has transactivation activity, and is upregulated by NaCl treatment. Salinity treatment resulted in the overexpressing transgenic tobacco lines generating significantly longer roots, with larger leaf area, higher fresh weight, and greater chlorophyll content than those of wild type (WT) plants. Moreover, the overexpressing lines showed elevated antioxidant enzyme activity, reduced malondialdehyde content, and leaf electrolyte leakage. In addition, the Na content significantly decreased, and the K /Na ratio was increased in the NtWRKY65 overexpression lines compared to those in the WT. These results suggest that NtWRKY65 overexpression enhances salinity tolerance in transgenic plants. RNA-Seq analysis of the NtWRKY65 overexpressing and WT plants revealed that NtWRKY65 might regulate the expression of genes involved in the salt stress response, including cell wall component metabolism, osmotic stress response, cellular oxidant detoxification, protein phosphorylation, and the auxin signaling pathway. These results were consistent with the morphological and physiological data. These findings indicate that NtWRKY65 overexpression confers enhanced salinity tolerance. Our results indicated that NtWRKY65 is a critical regulator of salinity tolerance in tobacco plants.